Why Market Freedoms are no Fundamental Rights: A Competence Approach - Stephan Gregor (Croatian Yearbook of European Law and Policy, 2010)
Market freedoms resemble in many aspects fundamental rights. Since individuals can invoke them against the measures of Member States, they are subjective rights which restrict the competence of the Member States in favour of the individual. Besides this most apparent function, market freedoms are also about the distribution of competence among Member States, and between Member States and the European Union. Market freedoms appear to confer the right to market access in the remaining area of their application. Thus, market freedoms seem to reserve an area of protection to the individual, which is necessary for them to be deemed fundamental rights. This area, however, is only reserved in relation to the Member States. According to the incompetence approach which is presented here, European institutions are bound by market freedoms only in an indirect way. It is just due to a lack of competence that a conflict between market freedoms and measures of European institutions seldom conflict. Since market freedoms do not strive for comprehensive protection in relation to any bearer of state authority, they lack the decisive feature of fundamental rights.